DFT calculation on relaxation and electronic structure of sulfide minerals surfaces in presence of H2O molecule - Chen, Jian-hua; Long, Xian-hao; Zhao, Cui-hua; Kang, Duan; Guo, Jin (Journal of Central South University, 2014)
First-principles calculations are performed to investigate the relaxation and electronic properties of sulfide minerals surfaces (MoS 2 , Sb 2 S 3 , Cu 2 S, ZnS, PbS and FeS 2 ) in presence of H 2 O molecule. The calculated results show that the structure and electronic properties of sulfide minerals surfaces have been influenced in presence of H 2 O molecule. The adsorption of the flotation reagent at the interface of mineral-water would be different from that of mineral surface due to the changes of surface structures and electronic properties caused by H 2 O molecule. Hence, the influence of H 2 O molecule on the reaction of flotation reagent with sulfide mineral surface will attract more attention.